Combined inhibition of TGFβ and PDGF signaling attenuates radiation-induced pulmonary fibrosis - Dadrich, Monika; Nicolay, Nils; Flechsig, Paul; Bickelhaupt, Sebastian; Hoeltgen, Line; Röder, Falk; Hauser, Kai; Tietz, Alexandra; Jenne, Jürgen; Lopez, Ramon; Roehrich, Manuel; Wirkner, Ute; et al. (OncoImmunology, 2016)
Background: Radiotherapy (RT) is a mainstay for the treatment of lung cancer, but the effective dose is often limited by the development of radiation-induced pneumonitis and pulmonary fibrosis. Transforming growth factor β (TGFβ) and platelet-derived growth factor (PDGF) play crucial roles in the development of these diseases, but the effects of dual growth factor inhibition on pulmonary fibrosis development remain unclear. Methods: C57BL/6 mice were treated with 20 Gy to the thorax to induce pulmonary fibrosis. PDGF receptor inhibitors SU9518 and SU14816 (imatinib) and TGFβ receptor inhibitor galunisertib were applied individually or in combinations after RT. Lung density and septal fibrosis were measured by high-resolution CT and MRI. Lung histology and gene expression analyses were performed and Osteopontin levels were studied. Results: Treatment with SU9518, SU14816 or galunisertib individually attenuated radiation-induced pulmonary inflammation and fibrosis and decreased radiological and histological signs of lung damage. Combining PDGF and TGFβ inhibitors showed to be feasible and safe in a mouse model, and dual inhibition significantly attenuated radiation-induced lung damage and extended mouse survival compared to blockage of either pathway alone. Gene expression analysis of irradiated lung tissue showed upregulation of PDGF and TGFβ-dependent signaling components by thoracic irradiation, and upregulation patterns show crosstalk between downstream mediators of the PDGF and TGFβ pathways. Conclusion: Combined small-molecule inhibition of PDGF and TGFβ signaling is a safe and effective treatment for radiation-induced pulmonary inflammation and fibrosis in mice and may offer a novel approach for treatment of fibrotic lung diseases in humans. Translational statement: RT is an effective treatment modality for cancer with limitations due to acute and chronic toxicities, where TGFβ and PDGF play a key role. Here, we show that a combined inhibition of TGFβ and PDGF signaling is more effective in attenuating radiation-induced lung damage compared to blocking either pathway alone. We used the TGFβ-receptor I inhibitor galunisertib, an effective anticancer compound in preclinical models and the PDGFR inhibitors imatinib and SU9518, a sunitinib analog. Our signaling data suggest that the reduction of TGFβ and PDGF signaling and the attenuation of SPP1 (Osteopontin) expression may be responsible for the observed benefits. With the clinical availability of similar compounds currently in phase-I/II trials as cancer therapeutics or already approved for certain cancers or idiopathic lung fibrosis (IPF), our study suggests that the combined application of small molecule inhibitors of TGFβ and PDGF signaling may offer a promising approach to treat radiation-associated toxicity in RT of lung cancer.